Little or unknown plants of the wild vascular flora of the Canary Island - Santos-Guerra, Arnoldo; Reyes-Betancort, Jorge Alfredo; Padrón-Mederos, Miguel Antonio; Mesa-Coello, Ricardo (Botanica Complutensis, 2013)
Twenty nine new taxa are added to the checklist of the canarian vascular flora. We also confirm that Epilobium angustifolium and Chamaecyse serpens are present in Tenerife and La Palma, respectively, and the chorology of Eleocharis palustris in La Gomera is extended. On the other hand Sida rhombifolia complex is revived in the Archipelago.